ANALISIS PENGGUNAAN DEIKSIS DALAM CERPEN BAHASA INDONESIA - Ach Zubairi; Ach Basri; Ach Zainuddin; Mas’odi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to analyze the use of deixis in Indonesian short stories, focusing on how these linguistic elements contribute to shaping the readers' perception of characters, setting, and plot. Deixis, as a part of pragmatic studies, refers to words or phrases whose meanings depend on the context of use, such as